Non‐nursing tasks as experienced by nurses: a descriptive qualitative study. (12th February 2019) - Grosso, S.; Tonet, S.; Bernard, I.; Corso, J.; De Marchi, D.; Dorigo, L.; Funes, G.; Lussu, M.; Oppio, N.; Pais dei Mori, L.; Palese, A.
Abstract : Background: Different concepts have been used to date (e.g. non‐nursing tasks, organizational work) to define tasks performed by clinical nurses other than nursing care. However, the true essence of nursing work is still poorly understood mostly because nurses are lacking an appropriate lexicon to describe their practice. Aims: To describe non‐nursing tasks as experienced by nurses, exploring antecedents and consequences as perceived in daily practice. Methods: A descriptive qualitative study from 2015 to 2016. A purposeful sample of nurses was approached. Semi‐structured interviews were used, and content analysis was performed on audio‐recorded and verbatim‐transcribed interviews. Findings: A total of 22 nurses participated, the majority of whom were female (16; 72.7%) and their average age was 42.6 years. The concept of 'Non‐nursing tasks' is limited in describing what nurses experience in daily practice; the concept of 'Being out of the nursing role' emerged as being fully descriptive of the nurses' experience and this can occur in two dimensions: outside and inside the role of other healthcare professions. The first dimension includes administrative work separating nurses from patients. The second dimension was reported to happen in proximity to patients but in three different directions towards professions requiring: (a) less education (e.g. healthcare assistants), (b) the same amount of education at university level (e.g. physiotherapists), and (c) higher education at university level as compared to nurses, thus performing activities expected by physicians. Antecedents of 'Being out of the nursing role' have been identified at the organizational, individual and educational levels; their consequences have been reported at the patient, professional and organizational levels. Conclusion: Nurses play various non‐nursing roles, below, above and in the horizontal levels, both inside and outside other healthcare professionals' role, mainly as a result of their felt moral obligation to offer the best to their patients, the organization's demand to nurses and the imprinting of nursing education. Implications for nursing/health policy: Strategies at the nursing professional and policy levels are needed aimed at (a) supporting nurses in optimizing their professional identity, (b) sharing their sense of moral obligation towards patients with other healthcare professionals, and (c) implementing models of care based on interprofessional cooperation.